2014
DOI: 10.1596/1813-9450-6748
|View full text |Cite
|
Sign up to set email alerts
|

School Resource and Performance Inequality: Evidence from the Philippines

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…If so, low-performing schools that also introduced SBM earlier were able to improve their test scores, regardless of SBM. It is also shown that the variation of NAT scores across schools has decreased in the same period consistently (Table A1), while variations in other conventional school and teacher resource inputs have increased during the same period (Yamauchi and Parandekar 2014). This is consistent with the observations in Table 2 as well as the findings in Tables 3 and 4, since the average NAT score of the SBM/2006 schools caught up to that of the SBM/2009 schools, which can be attributed at least partially to the introduction of SBM.…”
Section: Estimation Inmentioning
confidence: 83%
“…If so, low-performing schools that also introduced SBM earlier were able to improve their test scores, regardless of SBM. It is also shown that the variation of NAT scores across schools has decreased in the same period consistently (Table A1), while variations in other conventional school and teacher resource inputs have increased during the same period (Yamauchi and Parandekar 2014). This is consistent with the observations in Table 2 as well as the findings in Tables 3 and 4, since the average NAT score of the SBM/2006 schools caught up to that of the SBM/2009 schools, which can be attributed at least partially to the introduction of SBM.…”
Section: Estimation Inmentioning
confidence: 83%
“…3 Also, research in the Philippines has shown that reducing the number of students per classroom is associated with better student learning outcomes, particularly in rural schools. 4 Ensuring that schools have adequate infrastructure of good quality is a central pillar of government efforts to improve education outcomes in the Philippines. Over the last five years, the government has been conducting a renewed reform effort to increase access to good quality basic education.…”
Section: Introductionmentioning
confidence: 99%
“…How do the resources available to schools and the systems that manage these resources differ among regions and socioeconomic groups? 4. School performance and resources.…”
Section: Introductionmentioning
confidence: 99%
“…Data was matched across school years to generate a panel dataset. A separate set of working papers(Yamauchi, 2012;Yamauchi and Parandekar, 2013) present analysis of the BEIS-NAT data to examine the impact of SBM and to analyze patterns of inequality regarding results and resources. A detailed field survey of 150 schools was also conducted to investigate SBM related issues.Three division field survey: The three divisions of Pangasinan II, Bohol and Surigao Del Sur were chosen as the sample divisions for the field survey.…”
mentioning
confidence: 99%